Analisis Tingkat Kesejahteraan Masyarakat Nelayan (Studi Kasus: Pada Kecamatan Medang Deras Kabupaten Batu Bara) - Delia Arifin; Gustami Harahap; Khairul Shaleh Saleh (Jurnal Ilmiah Pertanian ( JIPERTA), 2019)
The life of fishing communities is a real state of affairs can be expressed through the efforts of those who are affected by fishing season, the natural conditions are not conducive, the limited capital and a low level of education resulting in weak socio-economic circumstances. The purpose of this research is to know the level of well-being of fishing communities Medang Deras Coal District. The sample in the study as many as 30 people who represent a population that is of traditional fishing communities in district of Medang Deras Coal District. Analysis of data obtained from research results are analyzed using a quantitative descriptive method. The data obtained through the dissemination of the questionnaire will be calculated frequencies and presentasenya is then presented in the form of a single table. Analysis of the results of the research level of traditional fishing communities in district of Medang Deras shows that 60% of the respondents were categorized.